Are my words good enough to eat?: the teaching and learning of specialized vocabulary in culinary studies - Nur Rasyidah Mohd Nordin,; Siti Hamin Stapa,; Saadiyah Darus, (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2015)
This article presents a review on the teaching and learning of vocabulary in the ESL classroom, specifically the acquisition of specialized vocabulary in hospitality and tourism. Past researches have shown that the size and coverage of vocabulary plays an important role in vocabulary acquisition, and that vocabulary learning can benefit from both intentional and incidental means. Studies on specialized vocabulary in Malaysian institutions of higher education have been very limited and past researches have focused on the English for Specific Purposes (ESP) for example business and medicine. There appears to be very few studies conducted within the culinary realm due to its infantile growth in Malaysia. The emergence of current interest into the hospitality and tourism related fields in the last few years in Malaysia provide promising future for both culinary students and educators. Thus, more research in culinary studies for L2 students are called for to further enhance its development for educational and commercial purposes in Malaysia.